A kind of black spherical silicon dioxide and preparation method thereof
The preparation of black spherical silica through the gradient heating calcining process of spherical organic silicone materials has been solved, and the problems of conductivity and thermal stability in the prior art have been achieved, and the unity of low whiteness and high insulation is achieved, which meets the needs of electronic substrate materials. , and reduce environmental pollution and process costs.
Patent Information
- Application Number
- CN202410991261.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-23
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-07-23
AI Technical Summary
In the prior art, when preparing black copper clad materials, the use of carbon-based carbon black and acetylene black and other materials leads to problems of conductivity and thermal stability, and aniline black contains toxic heavy metals, causing environmental pollution, affecting insulation performance and process costs.
After the unsaturated alcohol pretreatment, the temperature rise gradient and time are controlled through the gradient temperature rise calcining process to form black spherical silica, achieving the unity of insulation and black characteristics, and reducing whiteness and carbon content. Avoid toxic pollution.
Prepare black spherical silica with low whiteness, high insulation and low carbon content, solves the problems of conductivity and thermal stability, meets the requirements of electronic substrate materials for insulation performance and low whiteness, reduces process costs, and Reduced environmental pollution.
Smart Images

Figure CN118619292B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of semiconductor packaging materials and relates to black spherical silicon dioxide and a preparation method thereof. Background Art
[0002] In recent years, due to the outstanding characteristics of low energy consumption and high efficiency of light-emitting diodes (LEDs), they are widely used in the fields of electrical indication, LED display screens, etc. The rapid development of LEDs has also driven the development of the copper clad laminate industry. In addition to basic insulation, copper clad laminates used for LEDs are also required to have high light-shielding properties to avoid the problem of energy waste and loss of brightness caused by the light of the LED light source passing through the back of the board as much as possible. In addition, conventional copper clad laminates used for circuit boards usually also require black properties to improve the processability of laser etching or cutting. The above purpose is usually achieved by adding pigments such as carbon black to the manufacture of semiconductor packaging materials and circuit substrate materials to dye them gray or black.
[0003] Chinese patent application CN101851390A discloses a black halogen-free epoxy resin composition and a covering film prepared using the same, using a small amount of carbon black powder to make it black and to shield the light, and using titanium dioxide to enhance the shielding effect, functionally giving the covering film a black characteristic. However, materials such as carbon black and acetylene black, which are mainly carbon, have good conductivity and will significantly affect the insulation performance of the copper clad laminate.
[0004] Chinese patent application CN113736142A discloses a method for preparing a semiconductor packaging material or substrate material, which uses spherical or amorphous polysiloxane as a raw material, raises the temperature to between 600°C and 800°C in an oxidizing gas atmosphere before the organic components in the polysiloxane particles are substantially completely oxidized, and performs heat treatment so that a dense silicon oxide layer is formed on the surface of the powder, and at the same time, the organic components inside the heat-treated powder are thermally decomposed into carbon elements; calcining is performed at a temperature greater than 800°C and less than 1100°C to condense the remaining silanol groups to obtain a black spherical or amorphous silicon oxide filler, and the black spherical or amorphous silicon oxide filler is densely filled and graded in a resin to form a semiconductor packaging material or substrate material, thereby solving the conductivity problem caused by acetylene black dyeing and the problem of difficult laser processing of silicon dioxide.
[0005] Similarly, Chinese patent application CN113603103A discloses a method for preparing semiconductor packaging materials and substrate materials, which uses spherical or amorphous polysiloxane as a raw material, performs heat treatment under non-oxidizing gas or vacuum to obtain a heat-treated powder, and the heat treatment temperature is between 600°C and 800°C, so that the organic base inside the heat-treated powder is thermally decomposed into carbon elements, and at the same time, the silanol groups on the surface of the heat-treated powder are condensed to form a surface dense layer; calcining at a temperature greater than 800°C and less than 1100°C to condense the remaining silanol groups to obtain a black spherical or amorphous silica filler, and the black spherical or amorphous silica filler is densely filled and graded in the resin to form a semiconductor packaging material and a substrate material, fundamentally solving the conductivity problem caused by the introduction of acetylene black dyeing.
[0006] However, the above method still has some problems, such as the method of directly adding black pigments: first, carbon black and acetylene black, which are mainly carbon, have good conductivity and will significantly affect the insulation properties of the copper clad laminate, while aniline black, a black pigment composed of benzene rings and nitrogen elements, will significantly affect the thermal stability of the copper clad laminate, and aniline black contains toxic heavy metal chromium, and the production process is not environmentally friendly and causes great pollution. Summary of the invention
[0007] The purpose of the present invention is to provide a black spherical silica having both black characteristics and insulating properties and a preparation method thereof. The spherical silica prepared by the method has the characteristic of extremely low whiteness and can be used in low-reflectivity electronic substrates, effectively solving a series of problems caused by the additional addition of black pigments in the preparation of some electronic substrate materials, such as environmental pollution and damage to the insulating properties of the substrate, while saving a certain amount of process costs.
[0008] The technical solution for achieving the purpose of the present invention is as follows:
[0009] A black spherical silica with a whiteness of ≤12 and a density of 2.05~2.20 g / cm 3 , hydroxyl content ≤120 μg / g.
[0010] Furthermore, the black spherical silica has a whiteness of ≤2.22 and a density of 2.12-2.16 g / cm 3 , hydroxyl content ≤74 μg / g.
[0011] The preparation method of the above-mentioned black spherical silica uses a spherical organic silicone material as a raw material, first pre-treats it by impregnation in an unsaturated alcohol, and then calcines it by gradient temperature increase. The specific steps are as follows:
[0012] (1) Under vacuum conditions, the spherical organic silicone material is pre-treated by immersing it in an unsaturated alcohol, and after the immersion is complete, the spherical organic silicone material is taken out and allowed to stand to remove excess unsaturated alcohol;
[0013] (2) The end temperature of the heating process is multiplied by the total time of the stage as the programmed temperature gradient, and a two-stage gradient temperature rise calcination process is adopted. The pre-treated spherical silicone material is first calcined in the front stage, starting from room temperature, and the programmed temperature gradient is controlled to be 1600~2200℃·h, and the temperature is raised to 800~1400℃ in a nitrogen atmosphere. Then, the back stage calcination is carried out, and the programmed temperature gradient is controlled to be 3000~6250℃·h, and the temperature is raised to 1200~1600℃ in a nitrogen atmosphere to obtain black spherical silica.
[0014] Preferably, in step (1), the number of carbon atoms contained in the alkyl substituent on the organic silicone is 1 to 8, and the particle size of the spherical organic silicone material is in the range of 0.5 to 10 μm. In the specific embodiment of the present invention, polymethyl silicone is taken as an example.
[0015] Preferably, in step (1), the unsaturated alcohol is selected from unsaturated alcohols with strong wettability such as isomeric decanol, cyclopropanecyclooctyne methanol (BCN-OH), etc. In a specific embodiment of the present invention, cyclopropanecyclooctyne methanol is taken as an example.
[0016] Preferably, in step (1), the immersion pretreatment time is 2 to 3 hours, and the standing time is 4 to 6 hours.
[0017] Preferably, in step (2), the high-temperature equipment used in the calcination process includes but is not limited to a vacuum tube furnace, an atmosphere sintering furnace, an oxygen-free carbonization kiln, an atmosphere rotary kiln, and the like, which are high-temperature equipment capable of calcining under different atmospheres.
[0018] Compared with the prior art, the present invention has the following advantages:
[0019] (1) The present invention first uses unsaturated alcohol with strong wettability to impregnate the raw material spherical organic silicone, so that the unsaturated alcohol fills the internal void space of the organic silicone, which is conducive to better condensation of hydroxyl groups and slowing down the escape of internal organic matter in the subsequent gradient program temperature rise calcination process. Furthermore, a two-stage gradient temperature rise calcination process is adopted to control the calcination time under different temperature rise gradients, so that the silanol groups of the spherical silicon are condensed, and the bound water is removed as much as possible while the organic matter is cracked into carbon to a greater extent, thereby obtaining spherical silica with dense condensation and partial cracking of organic matter, and its appearance shows black characteristics.
[0020] (2) The spherical silica prepared by the method of the present invention can simultaneously achieve the contradictory unity of insulation and black properties, and prepare black core-shell spherical silica with low L*, a*, b* values and high carbon content. The specific indicators are shown in Table 1. The present invention achieves the characteristics of insulation and low whiteness by calcining the hydroxyl groups on the surface of spherical silica and carbonizing the organic matter at the same time, and solves the problem of high toxicity and pollution of black pigments in electronic materials, meets the requirements of electronic substrate materials such as copper clad laminates (CCLs) for insulation performance and low whiteness, and can be applied to the fields of materials such as light-absorbing coatings, CCLs, epoxy molding compounds (EMCs), and other electronic packaging and substrate fields that require opacity.
[0021] Table 1 Indexes of black core-shell spherical silica products
[0022] BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a scanning electron microscope image of the black spherical silica prepared in the present invention;
[0024] Figure 2 This is a transmission electron microscope image of the black spherical silica prepared in the present invention. DETAILED DESCRIPTION
[0025] The present invention is further described in detail below in conjunction with specific embodiments and drawings.
[0026] Example 1
[0027] Under normal temperature and vacuum conditions, 30 kg of polymethyl silicone raw material was immersed in cyclopropane cyclooctyne methanol for 2 hours, then taken out and left to stand for 4 hours to remove excess unsaturated alcohol. The impregnated polymethyl silicone was added to the high-temperature equipment, and the high-temperature equipment temperature program was set. The starting temperature was room temperature, the front-stage program temperature gradient was 1600℃·h, the end temperature was 800℃, the time period was 2h, and the rear-stage program temperature gradient was set to 4800℃·h, the end temperature was 1200℃, the time period was 4h, and the nitrogen atmosphere was maintained throughout the process. After the calcination was completed, it was allowed to cool naturally and the material was discharged to obtain a total of 29.6 kg of black spherical silica with a yield of 98.6%. The various index data of the product are shown in Table 2.
[0028] Comparative Example 1
[0029] This comparative example is basically the same as Example 1, except that the polymethyl silicone raw material is not impregnated, and a total of 29.5 kg of black spherical silica is obtained, with a yield of 98.3%. The index data of the product are shown in Table 2.
[0030] Comparative Example 2
[0031] Under normal temperature and vacuum conditions, 30 kg of polymethyl silicone raw material was immersed in cyclopropane cyclooctyne methanol for 2 hours, then taken out and left to stand for 4 hours to remove excess unsaturated alcohol. The impregnated polymethyl silicone was added to the high-temperature equipment, and the high-temperature equipment heating program was set. The starting temperature was room temperature, and the temperature was continuously raised to 1300 ° C for insulation. The total process time period was 7 hours, and the nitrogen atmosphere was maintained throughout the process. After the calcination was completed, it was allowed to cool naturally and the material was discharged to obtain a total of 29.6 kg of black spherical silica with a yield of 98.6%. The various index data of the product are shown in Table 2.
[0032] Table 2
[0033]
[0034] According to Table 2, by comparing Example 1 with Comparative Example 1, it can be seen that the whiteness of the product can be further reduced by performing two-stage programmed gradient heating after the polymethyl silicone raw material is impregnated; by comparing Example 1 with Comparative Example 2, it can be seen that compared with the traditional one-stage programmed heating, the two-stage programmed heating of the present invention can further reduce the whiteness of the product.
[0035] Example 2
[0036] Under normal temperature and vacuum conditions, 30 kg of polymethyl silicone raw material was immersed in cyclopropane cyclooctyne methanol for 2 hours, then taken out and left to stand for 4 hours to remove excess unsaturated alcohol. The impregnated polymethyl silicone was added to the high-temperature equipment, and the high-temperature equipment temperature program was set. The starting temperature was room temperature, the front-stage program temperature gradient was 1600℃·h, the end temperature was 800℃, the time period was 2h, and the rear-stage program temperature gradient was set to 5200℃·h, the end temperature was 1300℃, the time period was 4h, and the nitrogen atmosphere was maintained throughout the process. After the calcination was completed, it was allowed to cool naturally and the material was discharged to obtain a total of 29.1 kg of black spherical silica with a yield of 97.0%. The various index data of the product are shown in Table 3.
[0037] Table 3
[0038]
[0039] Example 3
[0040] Under normal temperature and vacuum conditions, 60 kg of polymethyl silicone raw material was immersed in cyclopropane cyclooctyne methanol for 2 hours, then taken out and left to stand for 4 hours to remove excess unsaturated alcohol. The impregnated polymethyl silicone was added to the high-temperature equipment, and the high-temperature equipment temperature program was set. The starting temperature was room temperature, the front stage program temperature gradient was 1600℃·h, the end temperature was 800℃, the time period was 2h, and the rear stage temperature setting program temperature gradient was 3000℃·h, the end temperature was 1200℃, the time period was 2.5h, and the nitrogen atmosphere was maintained throughout the process. After the calcination was completed, it was allowed to cool naturally and the material was discharged to obtain a total of 59.3 kg of black spherical silica with a yield of 98.8%. The various index data of the product are shown in Table 4.
[0041] Comparative Example 3
[0042] Under normal temperature and vacuum conditions, 60 kg of polymethyl silicone raw material was immersed in cyclopropane cyclooctyne methanol for 2 hours, then taken out and left to stand for 4 hours to remove excess unsaturated alcohol. The impregnated polymethyl silicone was added to the high-temperature equipment, and the high-temperature equipment temperature program was set. The starting temperature was room temperature, the front stage program temperature gradient was 1200℃·h, the end temperature was 600℃, the time period was 2h, and the rear stage temperature setting program temperature gradient was 3000℃·h, the end temperature was 1200℃, the time period was 2.5h, and the nitrogen atmosphere was maintained throughout the process. After the calcination was completed, it was allowed to cool naturally and the material was discharged to obtain a total of 59.5 kg of black spherical silica with a yield of 99.1%. The various index data of the product are shown in Table 4.
[0043] Comparative Example 4
[0044] Under normal temperature and vacuum conditions, 110 kg of polymethyl silicone raw material was immersed in cyclopropane cyclooctyne methanol for 2 hours, then taken out and left to stand for 4 hours to remove excess unsaturated alcohol. The impregnated polymethyl silicone was added to the high-temperature equipment, and the high-temperature equipment heating program was set. The starting temperature was room temperature, the front-stage program temperature gradient was 2250℃·h, the end temperature was 1500℃, the time period was 1.5h, and the rear-stage temperature gradient was set to 3000℃·h, the end temperature was 1200℃, the time period was 2.5h, and the nitrogen atmosphere was maintained throughout the process. After the calcination was completed, it was allowed to cool naturally and the material was discharged to obtain a total of 107.7 kg of black spherical silica with a yield of 97.9%. The various index data of the product are shown in Table 4.
[0045] Table 4
[0046]
[0047] According to Table 4, it can be seen from the comparison between Example 3 and Comparative Examples 3-4 that when the temperature ramp in the front stage or the end point temperature is too low or too high, the whiteness of the product will decrease.
[0048] Example 4
[0049] Under normal temperature and vacuum conditions, 110 kg of polymethyl silicone raw material was immersed in cyclopropane cyclooctyne methanol for 2 hours, then taken out and left to stand for 4 hours to remove excess unsaturated alcohol. The impregnated polymethyl silicone was added to the high-temperature equipment, and the high-temperature equipment heating program was set. The starting temperature was room temperature, the front-stage program temperature gradient was 2100℃·h, the end temperature was 1400℃, the time period was 1.5h, and the rear-stage temperature gradient was set to 6200℃·h, the end temperature was 1550℃, the time period was 4h, and the nitrogen atmosphere was maintained throughout the process. After the calcination was completed, it was allowed to cool naturally and the material was discharged to obtain a total of 108.9 kg of black spherical silica with a yield of 99.0%. The various index data of the product are shown in Table 5.
[0050] Table 5
[0051]
[0052] Example 5
[0053] Under normal temperature and vacuum conditions, 30kg of polymethyl silicone raw material was immersed in cyclopropane cyclooctyne methanol for 2h, then taken out and left to stand for 4h to remove excess unsaturated alcohol. The impregnated polymethyl silicone was added to the high-temperature equipment, and the high-temperature equipment heating program was set. The starting temperature was room temperature, the front-stage program temperature gradient was 2200℃·h, the end temperature was 1100℃, the time period was 2h, and the rear-stage temperature gradient was set to 4050℃·h, the end temperature was 1350℃, the time period was 3h, and the nitrogen atmosphere was maintained throughout the process. After the calcination was completed, it was allowed to cool naturally and the material was discharged to obtain a total of 29.3kg of black spherical silica with a yield of 97.6%. The various index data of the product are shown in Table 6.
[0054] Comparative Example 5
[0055] Under normal temperature and vacuum conditions, 30 kg of polymethyl silicone raw material was immersed in cyclopropane cyclooctyne methanol for 2 hours, then taken out and left to stand for 4 hours to remove excess unsaturated alcohol. The impregnated polymethyl silicone was added to the high-temperature equipment, and the high-temperature equipment heating program was set. The starting temperature was room temperature, the front-stage program temperature gradient was 2200℃·h, the end temperature was 1100℃, the time period was 2h, and the air atmosphere was maintained. The rear-stage temperature gradient was set to 4050℃·h, the end temperature was 1350℃, the time period was 3h, and the nitrogen atmosphere was maintained. After the calcination was completed, it was allowed to cool naturally and the material was discharged to obtain a total of 28.7 kg of black spherical silica with a yield of 95.6%. The various index data of the product are shown in Table 6.
[0056] Table 6
[0057]
[0058] According to Table 6, by comparing Example 5 and Comparative Example 5, it can be seen that the final product has a higher degree of hydroxyl condensation, a lower whiteness, and is denser and tighter overall than the process with air atmosphere in the front and nitrogen atmosphere in the back.
[0059] Example 6
[0060] Under normal temperature and vacuum conditions, 100 kg of polymethyl silicone raw material was immersed in cyclopropane cyclooctyne methanol for 2 hours, then taken out and left to stand for 4 hours to remove excess unsaturated alcohol. The impregnated polymethyl silicone was added to the high-temperature equipment, and the high-temperature equipment heating program was set. The starting temperature was room temperature, the front-stage program temperature gradient was 2000℃·h, the end temperature was 800℃, the time period was 2.5h, and the rear-stage temperature gradient was set to 5600℃·h, the end temperature was 1600℃, the time period was 3.5h, and the nitrogen atmosphere was maintained throughout the process. After the calcination was completed, it was allowed to cool naturally and the material was discharged to obtain a total of 98.7 kg of black spherical silica with a yield of 98.7%. The various index data of the product are shown in Table 7.
[0061] Comparative Example 6
[0062] Under normal temperature and vacuum conditions, 100 kg of polymethyl silicone raw material was immersed in cyclopropane cyclooctyne methanol for 2 hours, then taken out and left to stand for 4 hours to remove excess unsaturated alcohol. The impregnated polymethyl silicone was added to the high-temperature equipment, and the high-temperature equipment heating program was set. The starting temperature was room temperature, the front-stage program temperature gradient was 2000℃·h, the end temperature was 800℃, the time period was 2.5h, and the rear-stage temperature gradient was set to 5100℃·h, the end temperature was 1700℃, the time period was 3h, and the nitrogen atmosphere was maintained throughout the process. After the calcination was completed, it was allowed to cool naturally and the material was discharged to obtain a total of 98.3 kg of black spherical silica with a yield of 98.3%. The various index data of the product are shown in Table 7.
[0063] Comparative Example 7
[0064] Under normal temperature and vacuum conditions, 100 kg of polymethyl silicone raw material was immersed in cyclopropane cyclooctyne methanol for 2 hours, then taken out and left to stand for 4 hours to remove excess unsaturated alcohol. The impregnated polymethyl silicone was added to the high-temperature equipment, and the high-temperature equipment heating program was set. The starting temperature was room temperature, the front-stage program temperature gradient was 2000℃·h, the end temperature was 800℃, the time period was 2.5h, and the rear-stage temperature gradient was set to 4750℃·h, the end temperature was 950℃, the time period was 5h, and the nitrogen atmosphere was maintained throughout the process. After the calcination was completed, it was allowed to cool naturally and the material was discharged to obtain a total of 98.6 kg of black spherical silica with a yield of 98.6%. The various index data of the product are shown in Table 7.
[0065] Table 7
[0066]
[0067] According to Table 7, it can be seen from the comparison between Example 6 and Comparative Examples 6-7 that when the temperature ramp in the front stage or the end point temperature is too low or too high, the whiteness of the product will decrease.
[0068] Example 7
[0069] Under normal temperature and vacuum conditions, 100 kg of polymethyl silicone raw material was immersed in cyclopropane cyclooctyne methanol for 2 hours, then taken out and left to stand for 4 hours to remove excess unsaturated alcohol. The impregnated polymethyl silicone was added to the high-temperature equipment, and the high-temperature equipment heating program was set. The starting temperature was room temperature, the front-stage program temperature gradient was 2200℃·h, the end temperature was 880℃, the time period was 2.5h, and the rear-stage temperature gradient was set to 6250℃·h, the end temperature was 1250℃, the time period was 5h, and the nitrogen atmosphere was maintained throughout the process. After the calcination was completed, it was allowed to cool naturally and the material was discharged to obtain a total of 97.9 kg of black spherical silica with a yield of 97.9%. The various index data of the product are shown in Table 8.
[0070] Table 8
[0071]
[0072] In summary, the black spherical silica particles prepared by the method of the present invention are complete, round and defect-free. Figure 1 As shown, the overall structure is a core-shell layered structure, such as Figure 2 As shown, it meets certain performance indicators such as L* value (illuminance, representing the depth of color from black to white), a* and b* values (representing the tendency of red-green and yellow-blue respectively, the lower the absolute value, the higher and more stable the blackness of the product).
Claims
1. A method for preparing black spherical silicon dioxide, characterized in that: The specific steps are as follows: (1) Under a vacuum environment, pre-treating a spherical organic silicone material by immersing it in an unsaturated alcohol, taking it out after the immersion is complete, and letting it stand to remove excess unsaturated alcohol, wherein the organic silicone is polymethyl silicone and the unsaturated alcohol is cyclopropanecyclooctynemethanol; (2) The end temperature of the heating process is multiplied by the total time of the stage as the programmed temperature gradient, and a two-stage gradient temperature rise calcination process is adopted. The pre-treated spherical organic silicone material is first calcined in the front stage, starting from room temperature, and the programmed temperature gradient is controlled to be 1600~2200℃·h, and the temperature is raised to 800~1400℃, and the atmosphere is nitrogen. Then, the back stage calcination is carried out, and the programmed temperature gradient is controlled to be 3000~6250℃·h, and the temperature is raised to 1200~1600℃, and the atmosphere is nitrogen, to obtain black spherical silica; the whiteness of the black spherical silica is ≤12, and the density is 2.05~2.20 g / cm 3 , hydroxyl content ≤120 μg / g.
2. The preparation method according to claim 1, characterized in that: In step (1), the immersion pretreatment time is 2 to 3 hours, and the standing time is 4 to 6 hours.
3. The preparation method according to claim 1, characterized in that: In step (2), the high-temperature equipment used in the calcination process is a vacuum tube furnace, an atmosphere sintering furnace, an oxygen-free carbonization kiln or an atmosphere rotary kiln.
4. The preparation method according to claim 1, characterized in that Black spherical silica whiteness ≤2.22, density 2.12~2.16g / cm 3 , hydroxyl content ≤74 μg / g.
